Clinical characteristics and treatment outcome of Candida tracheobronchitis. Issue 6 (12th February 2021) - Gil, Hyun-Il; Yang, Bumhee; Lee, Taebum; Kim, Min Yeong; Choi, Hayoung; Yoo, Hongseok; Kim, Hojoong; Kwon, O. Jung; Chung, Sung Jun; Lee, Hyun
Abstract : Abstract: Although Candida species can cause invasive fungal diseases, such as disseminated infection and pneumonia, they rarely cause tracheobronchitis, which is often fatal. To identify the clinical characteristics of Candida tracheobronchitis, we retrospectively evaluated 8 patients who had pathologically proven Candida tracheobronchitis. Their median age was 64 (range: 51–70) years and 5 were females. Three patients had solid cancers and 5 had hematological malignancies. We classified tracheobronchitis into localized and diffuse types. Of the 8 patients, 5 had localized and 3 had diffuse tracheobronchitis. While all patients with diffuse tracheobronchitis had predisposing risk factors for invasive fungal disease, such as prolonged corticosteroid use, recent use of nucleoside analogues, or recent neutropenia (<500/m 3 ), only 2 of the 5 with localized tracheobronchitis had predisposing risk factors. Four of the 5 patients with localized tracheobronchitis had loco-regional bronchial mucosal damage (e.g., radiation or photodynamic therapy). Although all 8 patients ultimately died, some improved with or without antifungal treatment. Two of the 5 patients (1 with localized and the other with diffuse tracheobronchitis) who received antifungal agents improved after treatment, and 1 patient with localized tracheobronchitis who did not receive antifungal treatment improved spontaneously. Two of the 3 patients with diffuse tracheobronchitis did not respond to antifungal treatment. Candida tracheobronchitis can present as both localized and diffuse types. While the former was influenced more by loco-regional mucosal damage, the latter was influenced more by the patient's immune status. The treatment outcomes were especially poor in patients with diffuse tracheobronchitis.